2021
DOI: 10.21037/jtd-20-1535
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive and robotic coronary artery bypass grafting—a 25-year review

Abstract: During the mid-1990s cardiac surgery started exploring minimally invasive methods for coronary artery bypass grafting (CABG) and has over a 25-year period developed highly differentiated and less traumatic operations. Instead of the traditional sternotomy mini-incisions on the chest or ports are placed, surgery on the beating heart is applied, sophisticated remote access heart lung machine systems as well as videoscopic units are available, and robotic technology enables completely endoscopic approaches. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 101 publications
(93 reference statements)
2
73
0
6
Order By: Relevance
“…(B) Growth in the number of robotic procedures during 2016–2019. (C) Growth in the number of robotic procedures during 1998–2019, including data by Pettinari et al ( 10 ). (D) Growth of active robotic cardiac centers in Europe during 2016–2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) Growth in the number of robotic procedures during 2016–2019. (C) Growth in the number of robotic procedures during 1998–2019, including data by Pettinari et al ( 10 ). (D) Growth of active robotic cardiac centers in Europe during 2016–2019.…”
Section: Resultsmentioning
confidence: 99%
“…A recent 25-year review reported on 1,762 RA-MIDCAB and 1,678 robotic TECAB procedures ( 10 ). RA-MIDCAB resulted in 6.6% conversion to larger incisions, 1.9% revision for bleeding, 0.4% stroke, and 0.4% mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review done by Bonatti J et al [20], reviewing a total of 74 patient series published between 1996 and 2019, shows that 27.8% of the reported robotic-assisted procedures represent multivessel CABGs. In this review, the operative times reached 5.3 ± 0.8 hours, the cumulative conversion rate was 10.3%, the perioperative mortality reached 1.3%, the mean length of hospital stay was 5.2 ± 1.6 days, and the 3-year survival was reported in 2 papers as 96% and 95.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, the operative times reached 5.3 ± 0.8 hours, the cumulative conversion rate was 10.3%, the perioperative mortality reached 1.3%, the mean length of hospital stay was 5.2 ± 1.6 days, and the 3-year survival was reported in 2 papers as 96% and 95.5%. [20,21] This approach has shown adequate short-term clinical results and represents the minimally invasive technique with the least tissue trauma; however, there are no studies available reporting the procedure's long-term results, procedure times are usually longer than the other presented techniques, the learning curve has shown to require a triple-digit number of repetitions for the surgeon and team to achieve a comfort level demanding long training sessions, and it is a procedure dependent on complex technology with limited access and high costs for the moment [20,21]…”
Section: Discussionmentioning
confidence: 99%
“…The entire procedure is performed on a beating heart and without the use of cardiopulmonary bypass. The detailed technique of RA-MIDCAB has been described elsewhere (8). Three ports were used to facilitate the robotic procedure while permitting the chest to be insufflated with CO 2 , including one camera port into the 4th intercostal space on the left anterior axillary line and two instrument ports in the 2nd and 6th intercostal spaces close to the left midclavicular line.…”
Section: Surgical Proceduresmentioning
confidence: 99%